ANALISIS BIAYA DAN KUALITAS HIDUP PASIEN RAWAT JALAN DM TIPE 2 DENGAN TERAPI GLIQUIDONE DIBANDINGKAN GLIMEPIRIDE DI RSUD SURAKARTA TAHUN 2021 - Hanifah, Inaratul Rizkhy; Sari, Ela Dewi Puspita; Harsono, Samuel Budi (Jurnal Farmasi Udayana, 2023)
Diabetes Mellitus type 2 is a degenerative disease suffered by patients for life. WHO estimates that Indonesia's number of people with diabetes will be around 21.3 million in 2030. Poor blood sugar control in DM patients impacts the decreasing quality of life and increasing health costs. The aim of this study was to analyze the cost of gliquidone therapy compared to glimepiride and the quality of life of outpatients with type 2 DM at the Surakarta Hospital in 2021. The research was conducted using a cross-sectional study design. The sample in this study was obtained through the purposive sampling method with patients who met the inclusion criteria. Cost analysis was carried out by calculating direct medical and non-medical costs, followed by calculating the RUB value to determine which therapy had the most cost-utility. This study was conducted in August-September 2021. Cost data includes total medical costs from hospitals and transportation costs. Quality of life value in this study was measured using the D-QOL questionnaire. The results showed that the RUB value was Rp. 5,389,203; U = 0.749 while glimepiride was Rp. 4,117.949; U = 0.754. The sensitivity test results showed that the cost of non-ADO drugs had the longest range, so it became the most influential factor. More cost-utility compared to gliquidone. Keywords: Oral antidiabetic, CUA, Diabetes Mellitus, Quality of life